Salmonid sensory system development is affected by climate change driven temperature increases - Aubree E. Jones; Matthew J. O’Donnell; Amy M. Regish; Jacqueline F. Webb (Scientific Reports)
Abstract Increases in water temperature due to global climate change are known to alter the course and timing of fish development. The mechanosensory lateral line (LL) system mediates flow-sensing behaviors vital for survival in fishes, but the effects of increased water temperatures resulting from climate change on its development have not been examined. Here LL development was documented in a cold-water salmonid (brook trout, Salvelinus fontinalis) reared at the thermograph of a long-term study stream (ambient) and two higher temperatures (+ 2 and + 4 °C) that reflect projected increases within their native range. At these two higher temperatures, fish reach crucial early life history transitions earlier (e.g., hatch, “swim-up” from gravel nests into the water column) and are larger in size through the parr (juvenile) stage. Early forming canal neuromast receptor organs are larger, and the process of canal morphogenesis is also accelerated suggesting potential consequences for neuromast function and presumably for LL-mediated behaviors. A potential mismatch between the timing of transitions in early life history stages, the ability to carry out LL-mediated behaviors (e.g., prey detection), and the timing of the seasonal emergence of their preferred prey, could have serious implications for cold-water salmonid ecology and survival.